2018
DOI: 10.1093/bioinformatics/bty002
|View full text |Cite
|
Sign up to set email alerts
|

DincRNA: a comprehensive web-based bioinformatics toolkit for exploring disease associations and ncRNA function

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(104 citation statements)
references
References 17 publications
0
102
0
Order By: Relevance
“…The top 3 gene classes are protein coding, pseudogene, and lncRNA genes. Although many studies have shown that non-coding RNAs play key roles in the complex regulatory networks in cell system, most of their functions are still missing (Cheng et al, 2018a;Cheng et al, 2018d;Peng et al, 2019b). Further computational methods and biological experiments are still needed to understand these unknown markers, such as using phynotypes, ontologies, deep learning methods, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The top 3 gene classes are protein coding, pseudogene, and lncRNA genes. Although many studies have shown that non-coding RNAs play key roles in the complex regulatory networks in cell system, most of their functions are still missing (Cheng et al, 2018a;Cheng et al, 2018d;Peng et al, 2019b). Further computational methods and biological experiments are still needed to understand these unknown markers, such as using phynotypes, ontologies, deep learning methods, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we calculate disease semantic similarities between 412 diseases using DincRNA online toolkit [70], and represent them by a 412 × 412 similarity matrix DD (Fig. 1b), where the value of the element of the DD, DD(d(i), d(j)), represents the DSS of d(i) and d(j).…”
Section: Ds D Imentioning
confidence: 99%
“…Correlation coefficients between the module Eigengenes and traits were calculated using Pearson's method. Glucocorticoid-related gene modules were defined as those with correlation coefficients greater than 0.5 (Cheng et al, 2018).…”
Section: Identification Of Glucocorticoid-related Gene Modulesmentioning
confidence: 99%